Three-dimensional finite element analysis of stress distribution in retention screws of different crown-implant ratios - Moraes, S. L D; Pellizzer, Eduardo Piza [UNESP]; Verri, Fellippo Ramos [UNESP]; Santiago, J. F.; Silva, J. V L (Taylor & Francis, 2013)
The retaining screw of the implant-supported dental prosthesis is the weakest point of the crown/implant system. Furthermore, crown height is another important factor that may increase the lever arm. Therefore, the aim of this study was to assess the stress distribution in implant prosthetic screws with different heights of the clinical crown of the prosthesis using the method of three-dimensional finite element analysis. Three models were created with implants (3.75 mm × 10 mm) and crowns (heights of 10, 12.5 and 15 mm). The results were visualised by means of von Mises stress maps that increased the crown heights. The screw structure exhibited higher levels of stresses in the oblique load. The oblique loading resulted in higher stress concentration when compared with the axial loading. It is concluded that the increase of the crown was damaging to the stress distribution on the screw, mainly in oblique loading. © 2013 Taylor & Francis.
Keywords: biomechanics; dental implants; finite element analysis; implant-supported dental prosthesis; mechanical stress